Ethics, the heart of leadership (Westport Praeger, 2004)
The study of ethics and leadership can be traced back to Aristotle and the Ancient Greeks. Against the backdrop of corporate, political, and religious scandal, a contemporary examination of the complex and subtle relationships between ethics and leadership could not be more timely. In this updated and expanded edition, Joanne Ciulla presents a unique collection of essays by philosophers, leadership scholars with backgrounds in industrial and organizational psychology, and management theorists. The authors tackle such profound questions as: How do leaders motivate followers to achieve their goals? What is the moral relationship between leaders and followers? Are ethical leaders driven by self-interest or altruism? What is the ethical value of a leader's accomplishments? Do their actions serve the greatest good? Featuring new essays by Bruce Avolio and Edwin Locke, Terry Price, Bernie Bass and Paul Steidlmeier, and a foreword by James MacGregor Burns, this book probes what the answers to these questions mean for today's leaders, offering hands-on insights into the ethical dynamics that make the heart of leadership tick.
Includes bibliographical references and index.
Keywords: Business ethics